Learning Activeness Affects the Ability to Understand Students' Mathematical Concepts Using Discovery Learning Model - Budi, Dian Setyo; Bintoro, Henry Suryo; Rahayu, Ratri (Journal of Education Technology, 2020)
Learning activeness is a provision that must be possessed by every student in learning mathematics because active learning affects the conceptual ability of students. The problem that was found by the researcher during the observation time was the low student learning activeness so that the students' ability to understand concepts was still low in learning mathematics. The purpose of this study was to analyze how much influence active learning has on the ability to understand mathematical concepts using discovery learning models. This research is a quantitative experiment with the one-shot case study design type. The sample in this study were 40 students of grade V SD. Data collection techniques consisted of a written test of the ability to understand concepts and observation of learning activeness. The data analysis technique in this study includes a simple linear regression test. Based on the research results, it shows that learning activeness has a positive and significant effect of 69.8% on the ability to understand mathematical concepts using discovery learning models. This means that if the higher the student's learning activeness, the higher the results of understanding the students' mathematical concepts.